2018
DOI: 10.1136/annrheumdis-2017-212496
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of monotherapy with sirukumab compared with adalimumab monotherapy in biologic-naïve patients with active rheumatoid arthritis (SIRROUND-H): a randomised, double-blind, parallel-group, multinational, 52-week, phase 3 study

Abstract: Sirukumab monotherapy showed greater improvements in DAS28 (ESR), but similar ACR50 response rates, versus adalimumab monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 27 publications
3
33
1
Order By: Relevance
“…The SIRROUND-H study investigated superiority of sirukumab (IL-6i) monotherapy over ADA monotherapy in MTX-IR, bDMARD naive patients. The study failed to meet one of its coprimary endpoints with no significant differences in ACR50% response rates at week 24; the other primary endpoint (DAS28-ESR mean change from baseline at week 24) was met 66…”
Section: Resultsmentioning
confidence: 98%
“…The SIRROUND-H study investigated superiority of sirukumab (IL-6i) monotherapy over ADA monotherapy in MTX-IR, bDMARD naive patients. The study failed to meet one of its coprimary endpoints with no significant differences in ACR50% response rates at week 24; the other primary endpoint (DAS28-ESR mean change from baseline at week 24) was met 66…”
Section: Resultsmentioning
confidence: 98%
“…In total, 21 studies evaluating bsDMARDs,52–72 18 studies evaluating boDMARDs73–90 and 21 studies evaluating tsDMARDs91–111 were included (online supplementary table S104). Overall, the incidence of major adverse events was low in all RCTs with mostly no differences between the active treatment and placebo or active comparator.…”
Section: Resultsmentioning
confidence: 99%
“…In phase III RCTs that included patients with RA refractory to treatment with csDMARDs and biologic DMARDs, sirukumab was superior to placebo in improving disease activity, physical function and health-related quality of life, as well as inhibiting radiographic disease progression 76,77 . However, monotherapy with sirukumab was similar but not superior to adalimumab and efforts to obtain regulatory approval in RA were terminated 78 . Phase II trials of olokizumab demonstrated therapeutic benefit, and phase III trials are ongoing 79 .…”
Section: Il-6 Inhibition In Ramentioning
confidence: 99%